2018
DOI: 10.1002/cpt.1177
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A4*22 Impairs the Elimination of Ticagrelor, But Has No Significant Effect on the Bioactivation of Clopidogrel or Prasugrel

Abstract: CYP3A enzymes participate in the elimination of ticagrelor and the bioactivation of clopidogrel and prasugrel. We studied the effects of functional CYP3A genetic variants (CYP3A4*22; rs35599367 and CYP3A5*3; rs776746) on the pharmacokinetics and pharmacodynamics of ticagrelor, clopidogrel, and prasugrel. Six healthy volunteers with the CYP3A4*1/*22 and CYP3A5*3/*3 genotype (CYP3A4*22 carriers), eight with the CYP3A4*1/*1 and CYP3A5*1/*3 genotype (CYP3A5 expressors), and 11-13 with the CYP3A4*1/*1 and CYP3A5*3/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 49 publications
4
20
2
Order By: Relevance
“…However, in our study, CYP3A4 and CYP3A5 did not show a significant role in explaining some of the response variability. Our results resembled those of Holmberg et al who found that neither CYP3A4 nor CYP3A5 genotypes affected clopidogrel area under the concentration-time curve or platelet inhibition in healthy volunteers (30). Furthermore, the G143E polymorphism (rs71647871) described in CES1 was associated with a decreased protein functionality (31).…”
Section: Influence Of Other Cyp Enzymes Ces1 and Pon1supporting
confidence: 88%
“…However, in our study, CYP3A4 and CYP3A5 did not show a significant role in explaining some of the response variability. Our results resembled those of Holmberg et al who found that neither CYP3A4 nor CYP3A5 genotypes affected clopidogrel area under the concentration-time curve or platelet inhibition in healthy volunteers (30). Furthermore, the G143E polymorphism (rs71647871) described in CES1 was associated with a decreased protein functionality (31).…”
Section: Influence Of Other Cyp Enzymes Ces1 and Pon1supporting
confidence: 88%
“…Ticagrelor, clopidogrel, and prasugrel are active platelet aggregation inhibitors metabolized by CYP3A4, used in cardiology and neurology. For ticagrelor, CYP3A4 ∗ 22 carriers showed an 89% higher area-under-the-plasma-concentration-time curve (AUC) and more pronounced platelet inhibition (43% vs. 21%) ( Holmberg et al, 2019 ) ( Supplementary Table 3 ). This increases risk of bleedings ( Becker et al, 2011 ).…”
Section: Cardiologymentioning
confidence: 99%
“…This increases risk of bleedings ( Becker et al, 2011 ). No significant correlation of CYP3A4 ∗ 22 with active metabolites of clopidogrel or prasugrel was found, although the authors stated that differences in clopidogrel and prasugrel pharmacokinetics <50% cannot be ruled out ( Holmberg et al, 2019 ). For sildenafil, metabolized by CYP3A4 in less active compounds, is used in patients with heart failure, CYP3A4 ∗ 22 carriers showed increased dose-adjusted concentrations ( de Denus et al, 2018 ).…”
Section: Cardiologymentioning
confidence: 99%
“…Li et al (15) showed that SCLO1B1 and CYP3A4/5 polymorphisms did not affect the pharmacokinetics and pharmacodynamics of ticagrelor treatment in healthy Chinese male subjects. Holmberg et al (16), also showed that although CYP3A4*22 (rs35599367 G>A) impairs elimination, it has no effect on the bioactivation of clopidogrel, and population-based genomics show that there is almost no variation in the frequency of CYP3A4*22 based on populations of diverse ancestry, and thus cannot explain the increased risk of bleeding in Asians. Tatarunas et al (17) demonstrated that the CYP4F2 rs3093135 TT allele has a higher antiplatelet effect of ticagrelor and more frequent nonprocedural bleeding during ticagrelor therapy, as compared with AA and AT variant carriers.…”
Section: Discussionmentioning
confidence: 99%